2007
DOI: 10.1038/sj.leu.2404619
|View full text |Cite
|
Sign up to set email alerts
|

Unbalanced translocation der(1;7)(q10;p10) defines a unique clinicopathological subgroup of myeloid neoplasms

Abstract: The unbalanced translocation, der(1;7)(q10;p10), is one of the characteristic cytogenetic abnormalities found in myelodysplastic syndromes (MDS) and other myeloid neoplasms. Although described frequently with very poor clinical outcome and possible relationship with monosomy 7 or 7q-(À7/7q-), this recurrent cytogenetic abnormality has not been explored fully. Here we analyzed retrospectively 77 cases with der(1;7)(q10;p10) in terms of their clinical and cytogenetic features, comparing with other 46 adult À7/7q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
83
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(94 citation statements)
references
References 27 publications
9
83
0
2
Order By: Relevance
“…Instead, in our series the five patients with der(1;7)(q10;q10) experienced a clinical outcome similar to that of normal karyotypes. Thus, in agreement with Sanada et al [39] and in contrast with Slovak et al [40], our result confirms that der(1;7)(q10;p10) truly defines a distinct MDS risk group with an OS and a LFS significantly better than those associated with 27 and del(7q).…”
Section: Discussionsupporting
confidence: 93%
“…Instead, in our series the five patients with der(1;7)(q10;q10) experienced a clinical outcome similar to that of normal karyotypes. Thus, in agreement with Sanada et al [39] and in contrast with Slovak et al [40], our result confirms that der(1;7)(q10;p10) truly defines a distinct MDS risk group with an OS and a LFS significantly better than those associated with 27 and del(7q).…”
Section: Discussionsupporting
confidence: 93%
“…Previous reports in MDS have suggested that 7q-or der(1;7) is prognostically better than monosomy 7 [9][10][11][12][13]. However, these studies mostly used univariate analysis in their evaluation of survival: Hasse et al [9] (a tendency toward better survival with 7q-compared to monosomy 7), Pozdnyakova et al [10] (better survival with 7q-or der(1;7) compared to monosomy 7), and Cordoba et al [11] (better survival with 7q-compared to monosomy 7).…”
Section: Resultsmentioning
confidence: 99%
“…However, these studies mostly used univariate analysis in their evaluation of survival: Hasse et al [9] (a tendency toward better survival with 7q-compared to monosomy 7), Pozdnyakova et al [10] (better survival with 7q-or der(1;7) compared to monosomy 7), and Cordoba et al [11] (better survival with 7q-compared to monosomy 7). Multivariable analysis was utilized in the study by Sanada et al [13] (better survival with der(1;7) compared to either 7q-or monosomy 7) but the results were confounded by the inclusion of patients with therapy-related MDS and those with multiple chromosome abnormalities. Most recently, Schanz et al [12] reported that 7q-was more favorable with regards to overall survival as compared to monosomy 7, when each was considered as a single abnormality, but their observation was internally inconsistent in that 7q-and monosomy 7 were considered equivalent for defining double abnormalities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations